Plastic Surgery and the Malpractice Industry. Issue 1 (24th December 2020) - Boyd, J. Brian; Moon, Harry K.; Martin, Susan; Mastrogiovanni, Dena B.
Abstract : Summary: The current status of the plastic surgeon in the medical liability spectrum and ways to avoid litigation are explored by using pooled national data from the Medical Professional Liability Association, private information from Applied Medico-Legal Solutions RRG, and a detailed literature search. The medical liability system in the United States costs $55.6 billion, or 2.4 percent of total health care spending. Plastic surgery accounts for 3.31 percent of reported claims and 3.16 percent of paid claims. Total payments for plastic surgeons represent 1.75 percent of the total paid for all specialties. Malpractice awards are relatively light for plastic surgeons. Nevertheless, they still have a 15 percent chance per year of being sued. However, 93 percent of cases will close with a dismissal or a settlement, and only 7 percent will go to trial. Of these, the plastic surgeon will prevail in 79 percent. Most importantly, 75 percent of all cases will result in no payment. To minimize the chances of a lawsuit, plastic surgeons should maintain excellent communication with their patients and participate in shared decision-making. They should take a leadership role and buy in to the performance of perioperative checklists, embrace patient education, and actively participate in Maintenance of Certification. They should be transparent in their dealings with patients by preoperatively declaring their policies on revisions, refunds, complications, and payments. Plastic surgeons must maintain complete and accurate medical records and participate in hospital-based programs of prophylaxis. They should be aware that postoperative infection is the single costliest adverse outcome and proactively deal with it.